THE ANALYSIS OF CONJUNCTIONS IN WRITING AN ENGLISH NARRATIVE COMPOSITION: A SYNTAX PERSPECTIVE - Paramita Kusumawardhani (Wanastra: Jurnal Bahasa dan Sastra, 2017)
The purpose of the research is to analyze about conjunctions as a part of syntax in writing an English narrative composition. Syntax is the study of the rules that govern the ways in which words combine to form phrases, clauses and sentences. Syntax is one of the major components of grammar. Noam Chomsky (2007) stated, “Syntax is the study of the principles and processes by which sentences are constructed in particular languages. Syntactic investigation of a given language has as its goal the construction of a grammar that can be viewed as a device of some sorts for producing the sentences of the language under analysis”. Conjunctions are also part of Syntax discussed in this paper. There are also parts of speech. There are eight parts of speech such as verbs, nouns, pronouns, adjectives, adverbs, prepositions, conjunctions and interjections. A conjunction connects words, phrases or clauses. Writing is related to composition and there 4 kinds of composition, they are: argumentation, description, exposition and narration. Data was taken from 20 learners’ English narrative compositions. They were taken by asking the learners to make an English narrative composition. After taking the data then classifying, analyzing and correcting were done. There were some kinds of syntax were found in the learners’ English narrative compositions, they are: 5 items of subordinate conjunctions, 3 items of coordinate conjunctions and 2 item of conjunctive adverbs. Keywords: Syntax, Conjunctions, Writing Narrative Composition